Debt shocks and the dynamics of output and inflation in emerging economies - John Beirne; Nuobu Renzhi (Asian Development Bank (ADB), 2024)
This paper empirically examines the impact of public debt shocks on output and inflation in 34 emerging market economies (EMEs) using panel local projections over the period 2000 to 2022. The estimated results show that real gross domestic product (GDP) falls significantly after an unanticipated increase in public debt while inflation rises. We also examine whether fundamental characteristics across EMEs could affect the impact of public debt shocks. The results suggest that higher initial debt levels, tighter domestic financial conditions, and lower income levels amplify the negative responses of real GDP, while tighter global financial conditions dampen the negative impacts of debt shocks. For inflation, the responses vary depending on economic-specific characteristics. We also find other nonlinearities in the dynamics, with EMEs facing more severe effects during recessionary periods.
Keywords: E62; F40; 330; public debt; GDP; inflation; emerging market economies